Análisis del contenido de la programación radiofónica dirigida a jóvenes del cantón Latacunga. - Ortiz Robles, María del Carmen (2018)
The radio programs in Latacunga produce a varied content that is directed to young people. It is foundationally the communication produced by the media. The radio programs of the city have messages according to the themes of entertainment, informational and educational. This Project hops to form a constructive critique of the youth radio programs of the city in order to obtain a better production of radio and content, according to the new challenges that radio to face at this time. The present research uses a qualitative and quantitative methodology in order to analyze the data of radio programming from young people in Latacunga. The childhood, in actuality, chose the programs according to their music and interests thematic. We analyzed if the programs and its content met the expectations of the listeners, keeping in mind the respective preferences of the audience in the local radio media. Finally, presented is this investigation are various alternatives, which allow a bettering of youth radio through programming, identification, knowledge, as well as an explanation of the newly introduced topics and music genders that support the needs of youth in Latacunga.